2016
DOI: 10.4238/gmr.15048482
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and agronomic analysis of intraspecific variability in Capsicum baccatum var. pendulum accessions

Abstract: Capsicum baccatum is one of the most important chili peppers in South America, since this region is considered to be the center of origin and diversity of this species. In Brazil, C. baccatum has been widely explored by family farmers and there are different local names for each fruit phenotype, such as cambuci and dedo-de-moça (lady's finger). Although very popular among farmers and consumers, C. baccatum has been less extensively studied than other Capsicum species. This study describes the phenotypic and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
2
15
0
3
Order By: Relevance
“…CIV, in turn, showed the highest values of VIT C (123.3 mg 100g -1 ) and FL (59.8 mm) (Table 4). Moura et al (2010) obtained mean values of VIT C similar to those found in this study, and verified the viability of using germplasm per se as a source of vitamin C. These two clusters together presented the highest values of important traits for industrial purposes such as production of sauces, paprika, and preserves, as mentioned by Faria et al (2013) and Leite et al (2016), in addition to cosmetic and pharmaceutical uses (Leite et al, 2016). Thus, accessions belonging to clusters CIII and CIV, accessions 2 and 3, are indicated for prospective studies aimed at the industrial market.…”
Section: Resultssupporting
confidence: 89%
“…CIV, in turn, showed the highest values of VIT C (123.3 mg 100g -1 ) and FL (59.8 mm) (Table 4). Moura et al (2010) obtained mean values of VIT C similar to those found in this study, and verified the viability of using germplasm per se as a source of vitamin C. These two clusters together presented the highest values of important traits for industrial purposes such as production of sauces, paprika, and preserves, as mentioned by Faria et al (2013) and Leite et al (2016), in addition to cosmetic and pharmaceutical uses (Leite et al, 2016). Thus, accessions belonging to clusters CIII and CIV, accessions 2 and 3, are indicated for prospective studies aimed at the industrial market.…”
Section: Resultssupporting
confidence: 89%
“…However, when comparing clusters formed by morpho-agronomic and molecular data, an agreement of 42%, considered low, was observed. Low correlation or even no correlation between morpho-agronomic and molecular data was reported in other studies [13,[65][66][67]. Molecular markers not related to the morphoagronomic traits evaluated used in the study should provide a plausible explanation for the absence or low correlation between formed clusters.…”
Section: Discussionmentioning
confidence: 54%
“…The results show that the accessions behaved differently for each evaluated trait, which allows gain in the selection process. Leite et al (2016) and Martinez et al (2017) found genetic variability among accessions of C. baccatum to quantitative traits related to plant, flower and fruits. Neitzke et al (2010) reported divergence among genotypes for plant and fruit traits in pepper with ornamental potential.…”
Section: Discussionmentioning
confidence: 99%